1997
DOI: 10.1016/s0550-3213(97)80768-7
|View full text |Cite
|
Sign up to set email alerts
|

Do muons oscillate?

Abstract: We develop a theory of the EPR-like effects due to neutrino oscillations in the π → µν decays. Its experimental implications are space-time correlations of neutrino and muon when they are both detected, while the pion decay point is not fixed. However, the more radical possibility of µ-oscillations in experiments where only muons are detected (as it has been suggested in hepph/9509261), is ruled out. We start by discussing decays of monochromatic pions, and point out a few "paradoxes". Then we consider pion wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
63
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 24 publications
7
63
0
Order By: Relevance
“…In quantum theory propagating particles must be described by moving wave packets (see, e.g., [19]). Let us recall the main features of this approach [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Wave-packets Approach To Neutrino Oscillationsmentioning
confidence: 99%
“…In quantum theory propagating particles must be described by moving wave packets (see, e.g., [19]). Let us recall the main features of this approach [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Wave-packets Approach To Neutrino Oscillationsmentioning
confidence: 99%
“…The mass neutrino oscillation problem is connected basically to the phase difference between different mass-eigenstate, a property intimately related to the basic principles of quantum mechanics. In the standard treatment of the neutrino oscillation, the condition of same-energy (samemomentum) with different momenta (energies) of the mass-eigenstates is introduced [2,4,5,14,15,16], which arises the same practically applied massive neutrino oscillation phase, however it is indicated that the unambiguous theoretical description of the massive neutrino oscillation phase will be involved in the wave packet formalism and not in the plane wave approximation [17]. Further, it is shown that the same energy or same momentum description is just the arbitrariness of the choice of the Lorentz frame in which it is valid, nothing to do with the physical argument [18].…”
Section: Introductionmentioning
confidence: 99%
“…[2] and those of refs. [5,8,9] is that, in the former, oscillations in the strangeness of the neutral kaon are predicted to give rise to oscillations in the Λs produced in association with the kaon. No such effect was predicted in refs.…”
mentioning
confidence: 99%